2011
DOI: 10.1038/emboj.2010.363
|View full text |Cite
|
Sign up to set email alerts
|

A role for the universal Kae1/Qri7/YgjD (COG0533) family in tRNA modification

Abstract: The YgjD/Kae1 family (COG0533) has been on the top-10 list of universally conserved proteins of unknown function for over 5 years. It has been linked to DNA maintenance in bacteria and mitochondria and transcription regulation and telomere homeostasis in eukaryotes, but its actual function has never been found. Based on a comparative genomic and structural analysis, we predicted this family was involved in the biosynthesis of N 6 -threonylcarbamoyl adenosine, a universal modification found at position 37 of tR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
158
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 141 publications
(170 citation statements)
references
References 89 publications
8
158
0
3
Order By: Relevance
“…mined that this enzyme is necessary for cell autonomous growth in Drosophila, as we previously showed for Tcs5 (Prpk) (23). Metazoans are composed of different cell types, therefore making the phenotype observed in tcs3 mutants even more complex than the ones observed in yeast and other unicellular organisms (15,16,18,21,50,51). However, in every case analyzed, the deficiency of these enzymes strongly impairs cellular growth and proliferation.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…mined that this enzyme is necessary for cell autonomous growth in Drosophila, as we previously showed for Tcs5 (Prpk) (23). Metazoans are composed of different cell types, therefore making the phenotype observed in tcs3 mutants even more complex than the ones observed in yeast and other unicellular organisms (15,16,18,21,50,51). However, in every case analyzed, the deficiency of these enzymes strongly impairs cellular growth and proliferation.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, considering the particular limiting nature of the initiator tRNA for cell and animal growth (5,7) and as this tRNA is modified by t 6 A, we were prompted to investigate the impact of t 6 A in whole animal context using Drosophila. All previous studies on t 6 A function and synthesis have been performed in unicellular organisms or cells in culture (15)(16)(17)(18)(19)(20)(21). In this study, we address for the first time the role of t 6 A in a metazoan.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…By strengthening the codon/anticodon interaction and ribosome entry, t 6 A 37 is believed to participate in the maintenance of the translational reading frame. This is supported by the increase in translational frameshifts in cells lacking the ability to form t 6 A 37 (13)(14)(15). Recent studies of the t 6 A 37 biosynthesis pathway have identified the following four proteins in Escherichia coli that are necessary and sufficient for in vitro formation of the modification: TsaC, TsaD, TsaE, and TsaB, also known as YrdC, YgjD, YjeE, and YeaZ, respectively (16).…”
mentioning
confidence: 81%